Exploring the influence of path environment factors on walking behavior in urban parks with configuration attribute control. - Wei Dong; Qi Kang; Gangkui Wang; Ruiqian Hou; Ping Liu (PLoS ONE)
The existing evidence regarding the influence of visual and physical environmental features of park pathways on walking behavior is limited and contentious, partly due to the lack of control over pathway configurational attributes and walking behavior measurement methods. This study addresses this gap by using space syntax and GPS to quantify the structural attributes and pedestrian counts within the pathways in Fengqing Park. Through stratified regression analysis, we examined the impact of environmental factors on walking behavior while controlling for pathway configurational attributes. The findings reveal that even after accounting for pathway configurational attributes, visual (R² = 0.223) and physical (R² = 0.173) environmental factors significantly affect walking behavior. Specifically, pathways with greater choice (β = 0.359, p < 0.01) and depth (β = 0.179, p < 0.05) are more favored. In terms of visual elements, landscape architecture (β = 0.143, p < 0.05) enhances walking behavior, while the presence of water bodies (β = -0.168, p < 0.01) negatively affects it. With respect to the physical environment, path width (β = 0.514, p < 0.01), length (β = 0.163, p < 0.05), and surface smoothness (β = 0.152, p < 0.05) play significant roles in influencing walking behavior. This study contributes to advancing our understanding of the impact of the environmental features of urban park pathways on walking behavior, reconciling research disparities in this domain, and providing guidance for the design and improvement of park pathways.